PENGARUH EKUITAS MEREK DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG KONSUMEN AXA MANDIRI MAPAN SEJAHTERA DI KOTA MATARAM - Baiq Dinna Widiyasti (Master of Management, Mataram University, 2016)
The objective of the study was to evaluate the influence of brand equity and service quality toward consumer repurchase intention of AXA Mandiri Mapan Sejahtera’s insurance in the city of Mataram. Associative research design was adopted as the study guide. Purposive sampling techniques were used in which 97 copies of the research instrument were administered to consumer of AXA Mandiri Mapan Sejahtera’s, city of Mataram, out of which 97 copies of questionnaire were filled and returned. Pearson Product Moment correlation was used to analyse the data generated from respondents. The findings revealed that brand equity and service quality have significant influence on consumer repurchase intention at 0,05 level (2-tailed). The result of the research shows both of the variables significantly affecting consumer repurchase intention. Furthermore, brand equity ranks the first follow by service quality. This research will help the management of insurance to understand and recognize the ranking of variables affecting consumer repurchase intention of AXA Mandiri Mapan Sejahtera’s insurance. Keywords: Insurance, Brand Equity, Service Quality, and Repurchase Intention.